Characterization of the scour cavity evolution around a complex bridge pier - Pedro Ramos (2015)
A study on the time development of local scour around a complex pier was developed using a small-scale model embedded in a sediment bed. A total of 15 laboratorial tests were performed at the Hydraulics Laboratory of the Faculty of Engineering of the University of Porto. The duration of each experiment was previously established to progressively characterize the scour cavity. After each experiment, the flume was gradually emptied to facilitate the application of close-range photogrammetry. The scour depth values resulting from the application of photogrammetry at the pile cap front agree well with the values obtained experimentally. The temporal development of the scour cavity is presented and discussed. Empirical formulas for the scour cavity time development and for the relation of scour depths to scour cavity volumes were obtained. The obtained three-dimensional models can also be used for calibration and validation of numerical models.